2020
DOI: 10.1186/s12864-020-6506-3
|View full text |Cite
|
Sign up to set email alerts
|

Zmat2 in mammals: conservation and diversification among genes and Pseudogenes

Abstract: Background Recent advances in genetics and genomics present unique opportunities for enhancing our understanding of mammalian biology and evolution through detailed multi-species comparative analysis of gene organization and expression. Yet, of the more than 20,000 protein coding genes found in mammalian genomes, fewer than 10% have been examined in any detail. Here we elucidate the power of data available in publicly-accessible genomic and genetic resources by querying them to evaluate Zmat2, a minimally stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Our investigations found that in addition to the strong conservation of the protein and of protein-coding exons, a remarkable feature about mammalian Zmat2 is the presence of pseudogenes in half of the species that we have examined to date [11]. Moreover, based on phylogenetic analysis, it appears that these pseudogenes are relatively recent additions to their respective genomes, and have each arisen independently of one another during speciation [11].…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…Our investigations found that in addition to the strong conservation of the protein and of protein-coding exons, a remarkable feature about mammalian Zmat2 is the presence of pseudogenes in half of the species that we have examined to date [11]. Moreover, based on phylogenetic analysis, it appears that these pseudogenes are relatively recent additions to their respective genomes, and have each arisen independently of one another during speciation [11].…”
Section: Introductionmentioning
confidence: 70%
“…Human ZMAT2 and other mammalian Zmat2 genes had been incompletely characterized in the Ensembl and UCSC genomic repositories, but as shown in our recent studies, they comprise a highly conserved series of orthologous genes and proteins [11]. In 17 of 18 mammalian genomes analyzed, Zmat2 was found to be a single copy gene, with the single exception being a tandem duplication identified in the opossum genome.…”
Section: Characterizing the Chicken Zmat2 Genementioning
confidence: 83%
See 2 more Smart Citations
“…29 Other recently published studies from our group have demonstrated that Zmat2 pseudogenes are present in at least 9 other mammalian species. 34 As the DNA sequence of each of these pseudogenes was more similar to the paralog from the homologous mammalian species than to other Zmat2 pseudogenes, it seems likely that each Zmat2 pseudogene arose independently subsequent to the divergence of each mammal from its closest ancestors. 34 population allelic variants: 0% 0.005% 0.009% The overall population prevalence of variant alleles for each segment of the protein is listed above the map, and the number of missense mutations in various cancers is found below.…”
Section: The Zmat2 Gene In Humans and Other Primatesmentioning
confidence: 99%